Low‐dose immune tolerance induction for severe hemophilia A inhibitor patients: Immunosuppressants are generally not necessary for inhibitor‐titer below 200 BU/mL - Zhengping Li; Jie Sun; Zekun Li; Zhenping Chen; Guoqing Liu; Wanru Yao; Xiaoling Cheng; Gang Li; Yingzi Zhen; Di Ai; Yaohan Zhou; Qianqian Mao; et al. (Wiley, 2024)
ABSTRACT Importance It remained unclear that the efficacy comparison between low‐dose immune tolerance induction (LD‐ITI) incorporating immunosuppressants (IS) when severe hemophilia A (SHA) patients had inhibitor‐titer ≥200 Bethesda Units (BU)/mL (LD‐ITI‐IS200 regimen) and LD‐ITI combining with IS when SHA patients had inhibitor‐titer ≥40 BU/mL (LD‐ITI‐IS40 regimen). Objective To compare the efficacy of the LD‐ITI‐IS200 regimen with that of the LD‐ITI‐IS40 regimen for SHA patients with high‐titer inhibitors. Methods A prospective cohort study on patients receiving LD‐ITI‐IS200 compared to those receiving LD‐ITI‐IS40 from January 2021 to December 2023. Both received LD‐ITI [FVIII 50 IU/kg every other day]. IS (rituximab + prednisone) was added when peak inhibitor tier ≥200 BU/mL in the LD‐ITI‐IS200 regimen and ≥40 BU/mL in the LD‐ITI‐IS40 regimen. Success is defined as a negative inhibitor plus FVIII recovery ≥66% of the expected. Results We enrolled 30 patients on LD‐ITI‐IS200 and 64 patients on LD‐ITI‐IS40, with similar baseline clinical characteristics. A lower IS‐use rate was discovered in the LD‐ITI‐IS200 regimen compared to the LD‐ITI‐IS40 regimen (30.0% vs. 62.5%). The two regimens (LD‐ITI‐IS200 vs. LD‐ITI‐IS40) had similar success rate (70.0% vs. 79.7%), median time to success (9.4 vs. 10.6 months), and annualized bleeding rate during ITI (3.7 vs. 2.8). The cost to success was lower for LD‐ITI‐IS200 than for LD‐ITI‐IS40 (2107 vs. 3256 US Dollar/kg). Among patients with peak inhibitor‐titer 40-199 BU/mL, 10 non‐IS‐using (on LD‐ITI‐IS200 regimen) and 28 IS‐using (on LD‐ITI‐IS40 regimen) had similar success rates (70.0% vs. 78.6%) and time to success (9.0 vs. 8.8 months). Interpretation In LD‐ITI, IS are not necessary for inhibitor titer <200 BU/mL.